Gone with the wind: An externality of earnings pressure - Liu, Zheng; Shen, Hongtao; Welker, Michael; Zhang, Ning; Zhao, Yang (Journal of Accounting and Economics, 2021)
We investigate an externality of earnings pressure from capital markets. We define earnings pressure as managers’ incentives to meet or beat earnings expectations. Using detailed establishment-level sulfur dioxide emission data from China covering 2003 to 2012, we find that firms with earnings pressure have higher intensity sulfur dioxide emissions. This effect is more pronounced when the strength of monitoring and regulatory enforcement is weak, when litigation risk is low, and when the public firm is not mandated to issue a corporate social responsibility report. Our study sheds light on how financial goals may conflict with environmental goals, and has important implications for academics, regulators and society.